Analysis of The Optimal Charging System on A Plant Sprayer Using A 100 Watt Capacity Solar Panels - Pastron Simanjorang; Winfronstein Naibaho; Tambos Augus Sianturi; Azarya.n.j. Siahaan; Jhon Sufriadi Purba (International Journal of Technology and Education Research, 2026)
Problems arise when the electrical energy generated by solar panels is not constant throughout the day due to changes in the sun’s position. One way to address this is to adjust the panel’s angle—either manually or automatically—in accordance with the sun’s movement. The objectives of this study are to analyze the electrical charging system of a plant sprayer equipped with a 100-watt solar panel, to determine the optimal angle for the solar panel to generate electrical energy, and to measure the voltage, current, and power produced by the solar panel during the battery charging process. The analysis method was used to determine the effect of variations in the solar panel angle on the voltage, current, and electrical power generated. The study aimed to identify the optimal angle for generating electrical energy to charge the pump system and to assess the performance of the solar-powered crop sprayer at various panel tilt angles during charging, based on field test results. Research Findings: Optimal Charging System: The battery charging system for the crop sprayer achieves optimal performance when a 100-watt solar panel is installed at a tilt angle of 20^∘. At this angle, the solar panel produces the highest average current (3.873 A) and the highest charging power (72.409 W) compared to a 10^∘ tilt or a 0^∘ flat position. Power Increase Characteristics: Changes in the tilt angle were found to affect the charging power linearly and in the same direction. Every 1° increase in tilt angle (up to the test limit of 20°) will increase the battery charging output of the sprayer by a constant 1.036 watts. The difference in power efficiency only becomes statistically significant when the angle is changed directly from the horizontal position (0°) to the optimal angle (20°). Conclusions from this study: Charging Time Conditions: The charging duration is not affected by changes in the solar panel tilt angle. This is due to the protection system in the sprayer’s Solar Charge Controller (SCC), which limits the maximum current threshold to ensure battery safety, thereby keeping the charging time constant.